Playing With Dreams - Workshop Playing Cards ... - Wang, Irina; Rasmus, Sirpa; Sarkki, Simo; Habeck, Otto; Burgess, Philip; Pekkarinen, Antti-Juhani; Eronen, Jussi (Zenodo, 2023)
This is a guide for facilitating future-oriented workshops in order to gather insight for research and support long term planning in nature-based livelihoods. Attached are also the self printing playing cards in multiple languages for use in the person workshops. These are provided in English, Finnish, Norwegian, North Sámi, Swedish and Norwegian. Attached are also instructions on how to print the playing cards for best results. Irina Wang was the lead designer. Developing more narratives around Arctic futures can help local communities, policy makers, and other actors anticipate plausible developments/surprises, understand ongoing dynamics, and aid in decision making. This workshop is designed to help articulate and develop the following aspects of scenario work: Systems understanding of past, present, and future dynamics Response and adaptation to plausible surprises that may unfold Desirable futures for stakeholders and decision makers to strive toward Time estimates given in this document are only ... : Our warmest thanks to all workshop participants and support for workshops that was received from the Natural Resources Institute Finland (Luke) and the Finnish Reindeer Herders' Association. We would like to thank Lapland University of Applied Sciences in Rovaniemi and Sámi Education Institute in Inari for invitations to pilot the workshop with their students. Mikko Jokinen, Ilona Mettiäinen, Tuuli Parviainen, Laura Post, Taru Rikkonen, Jaana Sorvali, Tuulia Väärälä are acknowledged for their valuable help in facilitating the workshops. Leena Rantamaula, Heidrun Matthes and Roza Laptander are acknowledged for their technical support for and participation in piloting the method and producing communication material. Marit Klemetsen Arneberg, Jarle Bjerke, Tim Horstkotte, Matias Paltto Burgess, Klemetti Näkkäläjärvi translated parts of the material into Norwegian, Swedish and Northern Sámi, or checked the translations made by others. Research personnel from the Arctic Centre (Finland) as well as communication ...